2020
DOI: 10.52547/jvesselcirc.1.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Compassion-focused Therapy and Mindfulness-based Stress Reduction on Cognitive Emotion Regulation among Patients with Coronary Heart Disease

Abstract: Background and Aim: Coronary artery disease is one of the psychosomatic diseases that is affected not only by biological factors but also by psychosocial factors. Therefore, this study aimed to compare the effectiveness of compassionfocused therapy (CFT) and mindfulness-based stress reduction (MBSR) on cognitive emotion regulation among patients with coronary heart disease. Materials and Methods: This quasi-experimental study was conducted based on a pretest-posttest control group design and follow-up. The sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Izanloo et al . [ 37 ] also showed that the CFT and Mindfulness Based Stress Reduction (MBSR) had a significant effect on emotion regulation in patients with COVID-19 disease. Compassion-based therapy is an essential structure for emotion regulation, because compassion itself is a kind of mindfulness that allows one to understand and accept the most painful emotions in life without being frustrated and anxious by them.…”
Section: Discussionmentioning
confidence: 99%
“…Izanloo et al . [ 37 ] also showed that the CFT and Mindfulness Based Stress Reduction (MBSR) had a significant effect on emotion regulation in patients with COVID-19 disease. Compassion-based therapy is an essential structure for emotion regulation, because compassion itself is a kind of mindfulness that allows one to understand and accept the most painful emotions in life without being frustrated and anxious by them.…”
Section: Discussionmentioning
confidence: 99%